АКАДЕМИЯЛЫҚ ЛИЦЕЙЛЕРДЕ Ө.ХОЖАНИЯЗОВ ДӨРЕТИЎШИЛИГИН ОҚЫТЫЎ - Алламбергенов, К.; Юсупов, Қ.А. (FAN va JAMIYAT, 2020)
The article deals with individual peculiarities of the creative work of the famous Karakalpak writer U.Khojaniyazov and his skill as an artist of a word.